TEKNOLOGI PEMBUATAN RANSUM DAN INTRODUKSI AYAM KUB BAGI MASYARAKAT DI KELURAHAN KOTO LUA KECAMATAN PAUH KOTA PADANG - Ridho Kurniawan Rusli; Gita Ciptaan; Mirnawati Mirnawati; Ahadiyah Yuniza (LPPM (Institute for Research and Community Services) Universitas Andalas Padang, 2023)
Balitbangtan Superior Kampung Chicken (KUB) is a superior native chicken due to selection from native chicken families for six generations conducted by the Indonesian Agency for Agricultural Research and Development. KUB chickens have faster growth compared to ordinary native chickens. This training program was conducted for the Koto Lua community, Pauh District, Padang City, West Sumatra. This activity aims to help the community by conducting training on making poultry rations using conventional feed ingredients. In addition, this activity also aims to introduce one of the potential local chickens producing meat and eggs, namely: KUB chicken. The methods used in this activity were counseling and discussion (conventional feed and KUB chickens), training (traditional preparation of ration), mentoring (KUB chicken rearing), and evaluation at the end of the activity. 100 KUB chickens are raised by the service team from 1-28 days (4 weeks); after that, the KUB chickens are given to 10 heads of families (10 chickens per head of family), provided they have raised chickens and have a chicken coop. This activity results in the community gaining knowledge about feed ingredients that can be used as poultry rations. Community-rearing chickens until 16 weeks of age achieve an average body weight of 1000–150 g/head. The conclusion from this activity is that the community is skilled in making rations and raising KUB chickens, with a survival rate of around 90%.